Pengaruh Diskon Flash Sale Dan Gratis Ongkir Terhadap Impulse Buying Melalui Media Sosial Tiktok Pada Mahasiswa Manajemen Upi ”Yptk” Padang Angkatan 2022 - Putri Aprilliany; Emil Salimi; Della Asmaria Putri (Jurnal Ekonomi dan Bisnis Digital, 2026)
This study aims to analyze the effect of flash sale discounts and free shipping promotions on impulse buying through TikTok social media among Management students of UPI "YPTK" Padang, Class of 2022. The rapid growth of social media, particularly TikTok, has transformed consumer purchasing behavior by providing various promotional features that encourage spontaneous buying decisions. This research employs a quantitative approach using a survey method. The population consists of Management students of UPI "YPTK" Padang, Class of 2022, while the sample is selected using purposive sampling. Data are collected through questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS software. The independent variables are flash sale discounts and free shipping, the intervening variable is TikTok social media, and the dependent variable is impulse buying. The findings are expected to explain the direct and indirect effects of flash sale discounts and free shipping on impulse buying through TikTok social media. This study is expected to provide useful insights for digital marketers in developing effective promotional strategies and serve as a reference for future researchers.